Functionalization of medical textiles - Natalija Sadretdinova; Sergey Bereznenko; Larisa Bilotska; Maria Pawłowa; Szafrańska Halina; Vitalii Bakal; Natalia Bereznenko (Communications in Development and Assembling of Textile Products)
An important basis for the creation of medical clothing is realization of the influence of various factors that arise in the interaction of elements of the system "man–clothes–production environment". Given the increasing technogenic burden on health of both medical staff and hospital patients, the assessment of the role of medical clothing in forming the energy balance of direct consumers is extremely relevant.